2017
DOI: 10.1111/oik.04268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant and pollinator traits on the maintenance of a food deceptive species within a plant community

Abstract: Model–mimic plant systems are well known. However, the conditions promoting the existence of such systems are still an enigma. We suggest that by focusing on floral similarity between model and mimic, reward levels offered by models, and pollinators’ ability to adjust foraging accordingly, the conditions can be better understood. Using spatially‐explicit modelling, we examined trait combinations that lead to the survival of deceptive species under a large range of mimic strategies, from Batesian mimicry to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 89 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…The findings of this study, together with those of previous Batesian floral mimicry studies, suggest the following possible relationships among plant species playing the role of model, mimic or alternative: the model has a beneficial effect on the fitness of the mimic (Ma et al., 2015; Newman et al., 2012), the model and alternative have a detrimental (competitive) effect on each other's fitness (Chittka & Schürkens, 2001), the mimic has a detrimental effect on the model and may have a beneficial effect on the alternative because a peak shift induced by the mimic can alter the competitive superiority/inferiority between the model and alternative (Lynn et al., 2005; this study) and the alternative may have a beneficial effect on the mimic by reducing the discrimination performance of pollinators (this study) while simultaneously having a detrimental effect by inducing a peak shift (Qu et al., 2017).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The findings of this study, together with those of previous Batesian floral mimicry studies, suggest the following possible relationships among plant species playing the role of model, mimic or alternative: the model has a beneficial effect on the fitness of the mimic (Ma et al., 2015; Newman et al., 2012), the model and alternative have a detrimental (competitive) effect on each other's fitness (Chittka & Schürkens, 2001), the mimic has a detrimental effect on the model and may have a beneficial effect on the alternative because a peak shift induced by the mimic can alter the competitive superiority/inferiority between the model and alternative (Lynn et al., 2005; this study) and the alternative may have a beneficial effect on the mimic by reducing the discrimination performance of pollinators (this study) while simultaneously having a detrimental effect by inducing a peak shift (Qu et al., 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, Qu et al. (2017), through mathematical modelling, suggested that the presence of alternative rewarding flowers in a community encourages pollinators to shift away from the model‐mimic system, thus making the maintenance of floral deception systems difficult. In the current study, however, the presence of alternative rewarding flowers only marginally decreased the visits to mimics, given that the proportion of visits to mimics in the total number of visits did not differ significantly between the MoMi and MoMiAl arrays in both experiments (Figure 4A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibria characterize the long-run growth rates of the species, which represent reproduction successes of the two species and can be defined as their fitness/payoffs in the long-run interactions. For additional relevant works, we refer to [5,10,30,32,34,35,36,38,39,46]. To our knowledge, the co-evolution between nectarless flowers and pollinators has not been modeled by evolutionary games.…”
mentioning
confidence: 99%
“…To compare the effects of each type of initial abundance on the outcome of the algal competition, a local sensitivity analysis was performed. The sensitivity analysis was conducted via a disturbance method through changes in the initial value of a target variable (±20% of the default value), with calculation of the sensitivity (S) as follows 56,57…”
mentioning
confidence: 99%